Effect of four types of dietary fiber on the technological quality of pasta - Bustos Shmidt, Mariela Cecilia (2011)
The development of dietary fiber-enriched foods permits to obtain products with functional properties but can cause several problems in technological quality. The aim of this study was to study the quality of pasta obtained by replacing bread wheat flour with resistant starch II (RSII), resistant starch IV (RSIV), oat bran (OB) and inulin (IN) with the purpose of improving their nutritional quality. RSII, RSIV, OB and IN were substituted for a portion of bread wheat flour at levels 2.5%, 5.0%, 7.5% and 10.0%. Cooking properties, amylose and inulin losses, color and texture were measured. Finally, nutritional quality of enriched pasta was evaluated by protein losses during cooking and total dietary fiber. Microstructure of pasta was analyzed by scanning electron microscopy. Addition of RSII into pasta formulation improved the quality of the final product. RSIV-enriched pasta presented an improvement in textural characteristics and OB affected cooking properties positively up to 5% of substitution. Inulin was lost during cooking; besides, its addition negatively affected the technological quality of pasta. The results obtained in this study prove that it is possible to elaborate pasta with acceptable cooking quality and with improved nutritional characteristics by adding 10% of RSII and RSIV and 5% of OB.